Online Monitoring of Composites with a Miniaturized Flexible Combined Dielectric and Temperature Sensor - Martina Hübner (Proceedings, 2017)
We present a foil based miniaturized impedance sensor combined with a temperature sensitive structure to be integrated in Carbon-Fiber-Reinforced-Polymer (CFRP). Commercially available sensors are too big and they weaken the CFRP. In contrast the influence of our miniaturized flexible sensor can be neglected due to its size (5 µm thick); it is in the range of the fibers’ diameter. The sensor can remain in the produced part without disruption and even be used for structural health monitoring. Our sensor will enable automated control of the curing process and improve the fabrication. This is the first time impedance and temperature sensing is combined in such a small size.